2018
DOI: 10.1103/physrevb.97.115442
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-field-controlled negative differential conductance in scanning tunneling spectroscopy of graphene npn junction resonators

Abstract: Negative differential conductance (NDC), characterized by the decreasing current with increasing voltage, has attracted continuous attention for its various novel applications. The NDC typically exists in a certain range of bias voltages for a selected system and controlling the regions of NDC in curves of current versus voltage (I-V) is experimentally challenging. Here, we demonstrate an unusual magnetic-field-controlled NDC in graphene npn junction resonators. The magnetic field not only can switch on and of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…1f. Previous studies demonstrated that the existence of an energy gap is necessary to observe the NDC in the tunneling spectra of graphene systems 30,31 . Therefore, the observed NDC is a clear signature that there is a gap between the low-energy VHSs and the remote bands in the topmost TBG, which agrees well with that observed in slightly TBG [9][10][11][12][13][14][20][21][22][23]32,33 .…”
mentioning
confidence: 99%
“…1f. Previous studies demonstrated that the existence of an energy gap is necessary to observe the NDC in the tunneling spectra of graphene systems 30,31 . Therefore, the observed NDC is a clear signature that there is a gap between the low-energy VHSs and the remote bands in the topmost TBG, which agrees well with that observed in slightly TBG [9][10][11][12][13][14][20][21][22][23]32,33 .…”
mentioning
confidence: 99%
“…9(a) and (b). The external magnetic fields quantize the continuous band stucture of graphene into discrete LLs [58,71,[131][132][133][134]. The probing STM tip, acting as a moveable top gate, bends the LLs of the region beneath the tip into the gaps between the LLs of the surrounding regions, which leads to an edge-free GQD beneath the tip with confined orbital states [16,17,22,23,126].…”
Section: Stm Tip-induced Edge-free Gqdsmentioning
confidence: 99%
“…The ballistic electron propagation in 2D materials allows the observation of analogies from optics [42,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. For example, it has been shown that an electron beam, which hits the interface of a pn junction, is refracted similar to a light beam at the interface of two different media.…”
Section: Introductionmentioning
confidence: 99%